Analisis Financial Distress dengan Metode Altman Z-Score Modifikasi, Grover dan Zmijewski pada KSPPS BMT Ummat Sejahtera Abadi Jepara Tutup Tahun Buku 2018 – 2022 - Tahiyatur Ratih El Surayya; Afridian Wirahadi Ahmad (Politeknik Negeri Padang, 2023)
The purpose of this study was to recognize early warning signs of bankruptcy through financial distress analysis at KSPPS BMT Ummat Sejahtera Abadi Jepara by applying the Modified Altman Z-Score Method, the Grover Method and the Zmijewski Method. The type of research applied is quantitative research with descriptive descriptions. The object of research is the financial reports of KSPPS BMT Ummat Sejahtera Abadi Jepara at the close of the 2018 - 2022 financial year. The statistical study in this study uses the calculation of financial ratios at KSPPS BMT Ummat Sejahtera Abadi from the financial distress analysis method. The conclusion of the study showed that KSPPS BMT Ummat Sejahtera Abadi Jepara did not face financial distress in the results of the modified Altman Z-Score method above the cut off value > 2.60, the score for 5 consecutive years was 3.7. 3,825. 4,145. 4,027. 3,978. The same results show that the KSPPS BMT Ummat Sejahtera Abadi Jepara is in good health with the score on the Grover Method showing a number above the cut off G ≥ 0.01, namely 2018 (0.76), 2019 (0.77), 2020 (0.84) , 2021 (0.79), 2022 (0.799). Likewise the score on the Zmijewski Method shows a number less than 0, namely -3.28. -3.40. -3.62. -3.97. -3.95 means that KSPPS BMT Ummat Sejahtera Abadi Jepara is in good health, not facing financial distress and far from symptoms of bankruptcy.